Contemporary Computing 4th International Conference, IC3 2011, Noida, India, August 8-10, 2011. Proceedings - Aluru, Srinivas; Bandyopadhyay, Sanghamitra; Catalyurek, Umit V.; Dubhashi, Devdatt P.; Jones, Phillip H.; Parashar, Manish; Schmidt, Bertil; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
This volume constitutes the refereed proceedings of the Fourth International Conference on Contemporary Computing, IC3 2010, held in Noida, India, in August 2011. The 58 revised full papers presented were carefully reviewed and selected from 175 submissions.
Keywords: Computer science; Computer Communication Networks; Computer software; Information storage and retrieval systems; Artificial intelligence; Computer Science; Computer Communication Networks; Artificial Intelligence (incl. Robotics).; Algorithm Analysis and Problem Complexity; Information Systems Applications (incl. Internet).; Information Storage and Retrieval; Computation by Abstract Devices